Resistensi Kultural dalam Sastra Anak: Kajian Postkolonial terhadap Biografi Tenas Effendi - Aris, Qori Islami; Syam, Essy (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2025)
This study examines cultural resistance in children's literature through a postcolonial analysis of "Tenas Effendy, Punggawa Melayu" by Dessy Wahyuni. Utilizing a qualitative approach with content analysis, this research explores how this biographical work for children functions as a form of cultural resistance in the context of postcolonial Indonesian literature. The findings reveal that the book effectively represents Malay identity as dynamic and evolving, employs various strategies of cultural resistance including the use of Malay language and emphasis on local wisdom, and positions Malay culture within the broader Indonesian national context. It successfully engages child readers with complex cultural concepts through accessible language, demonstrating the potential of children's literature in preserving and revitalizing local culture. The book also portrays a negotiation between tradition and modernity, highlighting the relevance of Malay culture in contemporary settings. This research underscores the significant role of children's literature in cultural preservation and in fostering multicultural understanding among young generations in Indonesia, while also contributing to the broader discourse on postcolonial children's literature.